Frozen planet [videorecording (DVD)] - Attenborough, David, 1926- (BBC Earth ; Distributed in the USA and Canada by Warner Home Video, 2012)
The Arctic and Antarctic remain the greatest wildernesses on Earth. The scale and beauty of the scenery and the sheer power of the elements, the weather, the rough ocean and the ice, is unmatched anywhere else on our planet. tells the compelling story of animals such as the wandering albatross, the adelie penguin and the polar bear, and paints a portrait that will take your breath away, at a moment when, melting fast, the frozen regions of our planet may soon be changed forever.